What Does Decolonisation Mean in Bolivia in Relation to the Position of Religion in the Country’s New Legislation and the New Curriculum? - Drange, Live Danbolt (Mission studies, 2015)
The article discusses challenges and obstacles in creating intercultural dialogue and coexistence across religious and cultural boundaries in a society that is ethnically and culturally multi-dimensional. Bolivian society has always been multicultural and multi-ethnic with a majority of indigenous peoples. The Roman Catholic Church has since colonization officially been dominating religious life and political power while evangelical churches have been growing considerably during the last decades. The majority of indigenous peoples have historically been oppressed by an elite of Spanish descent. In the last few decades there has been an ethnic revitalizing and indigenous representatives have for the first time in history gained positions in the government. They have taken an active part in the rewriting of the Constitution and an education act intending to create a more just and equal society under the slogan “decolonize the state”. A new Constitution and Education Act are establishing that the state is secular and that it guarantees freedom of religion and belief at the same time as it is marked by Andean spirituality. This spirituality and the position of religion in society and in education have been topics of controversy in the process of constructing new legislation. In the discussion the Catholic Church, evangelical Christians and indigenous participants advocating traditional Andean spirituality have been participating. I will look in to possible consequences of this Andeanization especially concerning the children’s religious upbringing.